2012
DOI: 10.1038/nutd.2012.25
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned media from (pre)adipocytes stimulate fibrinogen and PAI-1 production by HepG2 hepatoma cells

Abstract: Background:Obesity is associated with a prothrombotic state, which may contribute to the increased risk of thrombotic events.Objective:To assess the effects of (pre)adipocyte-derived adipokines on fibrinogen, plasminogen activator inhibitor-1 (PAI-1) and tissue factor (TF) production by hepatocytes.Methods:HepG2 hepatocytes were incubated with conditioned media (CM) derived from preadipocytes and adipocytes, which had been untreated or prestimulated with tumor necrosis factor (TNF)-α, interleukin (IL)-1β or IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Adipocyte stimulation of spleen cell production of inflammatory cytokines such as IL-6 was expected and consistent with their own capacity to produce inflammatory mediators such as IL-1, TNF-α and IL-6 [13]. However, the increased production of IL-6 did not come from either CD4 + or CD8 + T-cells.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Adipocyte stimulation of spleen cell production of inflammatory cytokines such as IL-6 was expected and consistent with their own capacity to produce inflammatory mediators such as IL-1, TNF-α and IL-6 [13]. However, the increased production of IL-6 did not come from either CD4 + or CD8 + T-cells.…”
Section: Discussionmentioning
confidence: 60%
“…It has been previously shown that adipocytes can produce immune mediators such as IL-6 and TNF-α [13]. However, our studies suggest that their immune capacity might not be limited to directly producing immune mediators, but may include modulation of other immune cells (diagrammed in Fig.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…While animal models used in diabetes have been very valuable in providing mechanistic insights, the underlying confounding factors of the other organs such as the pancreas and brain can seldom be ruled out in the in vivo studies [6]. Moreover, since functional culture of primary cells such as primary hepatocytes is challenging, the in vitro studies that are conducted using modified immortalized cell lines provide limited value [7][8][9]. An alternative is to use microfluidic organ-on-chips that offer a controlled microenvironment to facilitate the physiological function of the cells.…”
Section: Introductionmentioning
confidence: 99%
“…Related to the mechanism in which the conditioned medium had beneficial effects, some considerations are needed to choose the cells to produce conditioned medium because different types of cells will secrete different proteins or growth factors. There are many sources of the cells to produce or harvest conditioned medium, such as mesenchymal stem cells, neural stem cells, or adipocyte-derived stem cells [ 9 10 11 12 ].…”
Section: Introductionmentioning
confidence: 99%